Frontispiece: Mechanical Trap Surface‐Enhanced Raman Spectroscopy for Three‐Dimensional Surface Molecular Imaging of Single Live Cells. Issue 14 (27th March 2017) - Jin, Qianru; Li, Ming; Polat, Beril; Paidi, Santosh K.; Dai, Aimee; Zhang, Amy; Pagaduan, Jayson V.; Barman, Ishan; Gracias, David H.
Abstract : Single Cell Imaging I. Barman, D. H. Gracias et al. present in their Communication onpage 3822 ff. a micromechanical SERS sensor for the simultaneous capture and visualization of the chemical composition of a single cellular surface.